2017
DOI: 10.17706/ijeeee.2017.7.3.191-201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Culture and Manufacturing Strategy on Firm Performance through Business Process Re-engineering

Abstract: Abstract:Many studies have focused on the direct impact of organizational culture, business process re-engineering, manufacturing strategy on the firm performance. This study examined the impact of organizational culture and manufacturing strategy on organization performance through business process re-engineering. Data were collected using questionnaires distributed to 111 respondents representing 37 cosmetics manufacturing firms located in the region of East Java, Indonesia. Statistical analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…As such, hotel facilities with a clear mission could significantly improve upon their performance levels. This finding is consistent with studies by Oberf€ oll et al (2018) and Siagian et al (2017). Siagian et al (2017) have found a mission to significantly influence the output of firms in East Java, Indonesia.…”
Section: Significance Of Path Coefficientssupporting
confidence: 92%
See 1 more Smart Citation
“…As such, hotel facilities with a clear mission could significantly improve upon their performance levels. This finding is consistent with studies by Oberf€ oll et al (2018) and Siagian et al (2017). Siagian et al (2017) have found a mission to significantly influence the output of firms in East Java, Indonesia.…”
Section: Significance Of Path Coefficientssupporting
confidence: 92%
“…This finding is consistent with studies by Oberf€ oll et al (2018) and Siagian et al (2017). Siagian et al (2017) have found a mission to significantly influence the output of firms in East Java, Indonesia. Lunenburg (2012) supported the importance of mission in improving an establishment's performance by asserting that successful companies often have a clear sense of mission and plan that defines business goals and strategic priorities and expresses a vision of how a business should look into the future.…”
Section: Significance Of Path Coefficientssupporting
confidence: 92%
“…Also, a study covered 37 manufacturing firms in Indonesia found a positive relationship between organizational culture and performance. However, manufacturing strategy was found to have stronger effect on performance than culture (Siagian et al, 2017). So, the following hypothesis was proposed:…”
Section: Industry Comparisonmentioning
confidence: 99%